(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the development of students’ self-preparation through the use of digital didactic technologies. It analyzes the integration of modern digital tools into the educational process, their effectiveness in enhancing learning outcomes, and their impact on students’ independent work skills. The paper also presents practical recommendations for improving software-didactic support in digital learning environments.